Growth Differentiation Factor-15 and Syndecan-1 Are Potential Biomarkers of Cardiac and Renal Involvement in Classical Fabry Disease under Enzyme Replacement Therapy - Paulo C. Gregório; Gilson Biagini; Regiane S. da Cunha; Júlia Budag; Ana Maria Martins; Lara Valiño Rivas; Elberth M. Schiefer; Maria Dolores Sánchez-Niño; Alberto Ortiz; Andréa E. M. Stinghen; Fellype C. Barreto (Kidney & Blood Pressure Research, 2022)
Background and Aims: Inflammation and endothelial damage play a pivotal role in Fabry disease (FD) manifestations. In daily clinical practice, FD is mainly monitored by traditional biomarkers of target organ injury, such as serum creatinine and proteinuria, which provide no information about inflammation and endothelial damage. Materials and Methods: We investigated the serum levels of 3-nitrotyrosine (3-NT), an oxidative stress biomarker, and of growth differentiation factor-15 (GDF-15) and syndecan-1 in classical FD patients on enzyme replacement therapy (ERT) for at least 6 months and their relationship with Fabry-related cardiac and renal manifestations. Results: Fifty-two classical FD patients (37 females) on ERT for 62.0 ± 27.5 months were included in the study. The main clinical manifestations included nephropathy (67.3%) and cardiomyopathy (21.1%). Serum levels of 3-NT, syndecan-1, and GDF-15 were 33.3 (4.8–111.1) nmol/mL, 55.7 (38.8–74.9) ng/mL, and 541.8 (392.2–784.4) pg/mL, respectively. There was a direct correlation between interventricular septal thickness and serum GDF-15 (r = 0.59; p < 0.001) and syndecan-1 (r = 0.30, p = 0.04). Among kidney parameters, there was a significant correlation between estimated glomerular filtration rate and GDF-15 (r = −0.61; p < 0.001), as well as between 24 h proteinuria and syndecan-1 (r = 0.28; p = 0.04). Serum GDF-15 levels were significantly higher in patients with cardiomyopathy (p = 0.03) as well in those with both nephropathy and cardiomyopathy (p = 0.02) than in patients without these comorbidities. Serum GDF-15 levels were also significantly higher in patients who started ERT at an older age (≥40 years). In multivariate analysis, syndecan-1, 3-NT, GDF-15, time on ERT, and arterial pressure differentiated Fabry patients with both cardiac and renal involvement from those without these manifestations. Conclusions: GDF-15 and syndecan-1 were associated with parameters of cardiac and renal involvement in classic FD patients on ERT. Their potential association with residual risk and disease outcomes should be investigated.